Clinical features of muscle stiffness in 37 dogs with concurrent naturally occurring hypercortisolism. (16th February 2023) - Golinelli, Stefania; Fracassi, Federico; Bianchi, Ezio; Pöppl, Álan Gomes; Miceli, Diego Daniel; Benedicenti, Leontine; De Marco, Viviani; Cook, Audrey K.; Espada Castro, Laura; Ramsey, Ian; Seo, Kyoung Won; Cantile, Carlo; et al.
Abstract: Background: Severe muscle stiffness (SMS) in dogs with hypercortisolism (HC) is uncommon. Objectives: To evaluate signalment, presentation, treatments, and long‐term outcomes of dogs with concurrent HC and SMS. Animals: Thirty‐seven dogs. Methods: Medical records of dogs with HC and concurrent SMS were recruited from 10 institutions. Clinical information, test results, therapeutic responses, and survival times were reviewed. Results: All 37 dogs with HC and SMS had pituitary‐dependent hypercortisolism (PDH); 36/37 weighed <20 kg. Signs and test results were typical of PDH aside from SMS, initially diagnosed in all 4 limbs in 9, pelvic limbs of 22, and thoracic limbs of 6 dogs. Hypercortisolism and SMS were diagnosed together in 3 dogs; HC 1‐36 months before SMS in 23; SMS 1‐12 months before HC in 11. Mitotane or trilostane, given to control HC in 36/37 dogs, improved or resolved HC signs in 28; SMS did not resolve, remaining static or worsening in 31/36 dogs, mildly improving in 5/19 dogs given additional therapies. Progression of SMS included additional limbs in 10 dogs and the masticatory muscles of 2. The median survival time from diagnosis of SMS was 965 days (range, 8‐1188). Conclusions and Clinical Importance: Concurrent SMS and HC is uncommon, possibly affecting only dogs with PDH. Development of SMS might occur before or after diagnosis of HC. Apart from SMS, the clinical picture and survival time of these dogs seem indistinguishable from those of dogs with HC in general. However, while muscle weakness usually resolves with HC treatment SMS does not.